Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasaan Pelanggan (Studi Kasus Pada Spbu Muara Siban Kecamatan Pulau Pinang Kabupaten Lahat - Markus, Markus (Universitas Muhammadiyah Palembang, 2020)
Purpose –The purpose of this research is to analyze how much influence partially and simultaneously between service quality and facilities in efforts to increase customer satisfaction at the Muara Siban Lahat gas station based on the background above. Design/methodology – This research uses the Accidental sampling method, namely sampling which is done by chance by distributing questionnaires to Muara Siban gas station customers, Lahat District, Lahat Regency. Data collection is done when the customer is buying fuel at the gas station. The research will be carried out at Muara Siban Lahat SPBU. The research used is a quantitative approach. Through this research, it can be used as input for managers of Muara Siban gas stations.Findings - The result of the multiple linear regression explanation above shows that the regression equation Y = 2.593 + 0.340 + 0.515, with an explanation of the constant value of 2.593 means that if the independent variable does not pay attention, the value of the Customer Satisfaction variable (Y) is 2.593. The results of the discussion of multiple linear regression obtained a variable value of Service Quality (X1) of 0.340, which means that if the Service Quality variable (X1) is increased by 0.340 it will increase the Customer Satisfaction variable (Y) by 0.340. The results of the discussion of multiple linear regression obtained the Facility variable value (X2) of 0.515 which means that if the Facility variable (X2) is increased by 0.515 it will increase Customer Satisfaction (Y) by 0.515.